Photocatalytic degradation of methylene blue dye solution using different amount of ZnO as a photocatalyst / Hartini Ahmad Rafaie … [et al.] - Mohd Yusop, Nur Fitrahana; Azmi, Nurathira Faqihah; Abdullah, Nur Syakirah; Ramli, Nurul Infaza Talalah (Faculty of Applied Sciences, 2021)
Zinc oxide (ZnO) powder was used as a photocatalyst for the photocatalytic degradation of methylene blue (MB) dye solution. In this study, different amount of ZnO (10, 20 and 30 mg) as photocatalyst was used to investigate the performance of photocatalytic degradation of MB dye solution. The morphology and structural properties of ZnO powder were studied by X-ray diffraction (XRD) and Field Emission Scanning Electron Microscope (FESEM) techniques. The photocatalytic activities of the ZnO powder were investigated by degrading the MB dye solution under UV light irradiation at different amounts of ZnO photocatalyst. The percentage degradation of MB dye solution in the presence of 10 mg ZnO powder was found to be the highest at 96.2 % within 60 min irradiation compared to 20 and 30 mg of ZnO powder. The photodegradation rate constants, k obtained in this study were 0.0661, 0.0558, and 0.0507 min-1 for 10, 20, and 30 mg ZnO powder, respectively that follow the pseudo first-order reaction kinetics.